Pick My Desk and Go: A solution to Improve Team Dynamics - Riccardo Bonazzi (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Dubrovnik, Croatia, 7-9 September 2017, 2017)
In this article, we describe the preliminary results of an ongoing project to improve the dynamics of innovative teams. We investigate how to design a system that allows employees in an open space to swap the place with a colleague for one day. We call this system “Pick my desk and go” and we combine notions from people analytics and organizational design to illustrate how the system enhances collaboration among team members and knowledge exchange. We tested the system for a period of eight weeks and we collected empirical evidences and insights from semi-structured interviews that support our claim concerning the effectiveness of the system to improve team creativity. We conclude the paper by illustrating the features of the next version of the system in order to increase its effectiveness as a persuasive system.
Keywords: M1; 330; people analytics; organizational design; behavioural change